High Expression of Hyaluronan-Mediated Motility Receptor Predicts Adverse Outcomes: A Potential Therapeutic Target for Head and Neck Squamous Cell Carcinoma - Lu, Tianzhu; Zheng, Yahan; Gong, Xiaochang; Lv, Qiaoli; Chen, Junjun; Tu, Ziwei; Lin, Shaojun; Pan, Jianji; Guo, Qiaojuan; Li, Jingao (Frontiers in Oncology, 2021)
Background: Several studies have shown that the hyaluronan-mediated motility receptor (HMMR)is overexpressed in various cancers and could be a potential prognostic factor. However, research is still required to determine the prognostic value and potential function of HMMR in head and neck squamous cell carcinoma (HNSCC). Materials and Methods: Transcriptomic expression data were collected from the Cancer Genome Atlas database (TCGA) and Gene Expression Omnibus and the differences in HMMR expression between normal and tumor tissues were analyzed. The correlation between the methylation level of HMMR and its mRNA expression was analyzed via cBioPortal. Additionally, the data obtained from TCGA was analyzed with MethSurv to determine the prognostic value of the HMMR methylation levels in HNSCC. Gene set enrichment analysis (GSEA) and single sample GSEA (ssGSEA) were used to explore the potential biological functions of HMMR. Results: HMMR was highly expressed in HNSCC tumor tissue compared to normal tissue (p < 0.001). Multivariate analysis (MAV) showed that high HMMR mRNA expression was an independent prognostic factor of overall survival (OS) in TCGA (HR = 1.628, p = 0.004) and GSE41613 data (HR = 2.238, p = 0.013). The methylation level of HMMR negatively correlated with the HMMR expression (R = −0.12, p < 0.001), and patients with low HMMR methylation had worse OS than patients with high methylation (p < 0.001). GSEA found that HMMR expression was associated with the KARS, EMT, and G2M checkpoint pathways, as well as the interferon-gamma and interferon-alpha responses, whereas ssGSEA showed that HMMR expression positively correlated with the infiltration level of Th2 cells. MAV confirmed that high HMMR protein expression was an inferior independent factor for OS (HR=2.288, p=0.045) and progression-free survival (HR=2.247, p=0.038) in 70 HNSCC. Conclusions: This study demonstrated that the upregulation of HMMR mRNA and protein in HNSCC is a biomarker for poor prognosis. The biological functions of HMMR are potentially related to the KARS, EMT, and G2M checkpoint pathways, as well as the interferon-gamma and interferon-alpha responses. These findings help to elucidate the role of HMMR in carcinogenesis and lay a foundation for further study.